Analysing student engagement with 360-degree videos through multimodal data analytics and user annotations. Issue 5 (19th October 2020) - Tan, Sabine; Wiebrands, Michael; O'Halloran, Kay; Wignell, Peter
ABSTRACT: This paper presents the findings from a case study which explores how students engage with learning materials mediated through 360-degree panoramic videos. The case study extends findings from a project which developed an online platform for viewing and annotating 360-degree videos, and for providing data analytics (heatmaps, viewpoint tracking and area of interest displays) to map student engagement with video content. In this case, information obtained from the data analytics forms the basis for the analysis which, taking a social semiotic perspective, explores (a) what multimodal resources in the video-recorded classroom activity function to attract and hold students' attention, and (b) what multimodal resources students employ when interacting with the 360-degree videos and for which purpose, taking the context into account. The findings indicate that for students to engage meaningfully with educational content requires familiarity with the demands of 360 video technology, which for some users can prove distracting, or even disabling.